Becoming an English Teacher: An Autobiographical Narrative Inquiry - Afrianto Daud (STAI Hubbulwathan Duri, 2021)
This paper documents a fragment of a story in my life that plays a significant role in shaping my identity as an English teacher and influencing me in deciding to become an English teacher as my career choice. This study's research question is 'how and why did I decide to become an English teacher?'. This study was conducted using the